2019
DOI: 10.1146/annurev-marine-010318-095150
|View full text |Cite
|
Sign up to set email alerts
|

The Scientific Legacy of the CARIACO Ocean Time-Series Program

Abstract: TheCARIACO(Carbon Retention in a Colored Ocean) Ocean Time-Series Program station, located at 10.50°N, 64.66°W, observed biogeochemical and ecological processes in the Cariaco Basin of the southwestern Caribbean Sea from November 1995 to January 2017. The program completed 232 monthly core cruises, 40 sediment trap deployment cruises, and 40 microbiogeochemical process cruises. Upwelling along the southern Caribbean Sea occurs from approximately November to August. High biological productivity (320-628 g C m y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 116 publications
3
55
0
3
Order By: Relevance
“…Biological production of organic particles in the euphotic zone is responsive to seasonal upwelling of nutrients with biomass maxima typically observed between December and May (Muller‐Karger, Astor, Benitez‐Nelson, et al, ). This is reflected in variations in the POC and PN concentrations in the upper 75 m of the water column over the entire observation period (Figures a and b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological production of organic particles in the euphotic zone is responsive to seasonal upwelling of nutrients with biomass maxima typically observed between December and May (Muller‐Karger, Astor, Benitez‐Nelson, et al, ). This is reflected in variations in the POC and PN concentrations in the upper 75 m of the water column over the entire observation period (Figures a and b).…”
Section: Resultsmentioning
confidence: 99%
“…The Cariaco Basin is 1,400‐m deep, located in a seasonal upwelling zone on the continental shelf of Venezuela and isolated from the Caribbean by a shallow sill (~100 m) with two channels extending only to about 150‐m water depth. A general description of carbon cycling in the basin and its relationship to global carbon cycling can be found in Muller‐Karger, Astor, Benitez‐Nelson, Buck, et al (). The basin has an oxic/anoxic transition zone, currently between ~250 and 300 m. Sampling for this entire study was conducted at a single site (10°30′N, 64°40′W), the primary sampling station of the Cariaco Ocean Time Series program (http://www.imars.usf.edu/cariaco), aboard the B/O Hermano Ginés , operated by Estación de Investigaciones Marinas (EDIMAR), Fundación La Salle de Ciencias Naturales located on Margarita Island, Venezuela.…”
Section: Methodsmentioning
confidence: 99%
“…In many anoxic marine zones, reductants such as hydrogen sulfide, ammonium, and the potent greenhouse gas methane, diffusing upwards from underlying layers or the sediments, react biologically with oxidants such as oxygen and nitrate produced in the overlying layers, thus fueling chemolithoautotrophic activity and affecting marine nitrogen, sulfur, oxygen, and carbon budgets (Taylor et al, ; Ulloa et al, ). In the Cariaco Basin, a permanently anoxic marine region off the coast of Venezuela, multi‐decadal monitoring has generated rich time series of the distribution of metabolically important compounds over space and time (Muller‐Karger et al, ; Scranton et al, ). These data revealed the existence of a strong dynamic redox gradient over depth, along which upward diffusing reductants such as hydrogen sulfide are directly or indirectly oxidized by oxidants such as oxygen in a transition zone roughly spanning depths 200–400 m, sometimes referred to as “redoxcline” (Ho et al, ; Li, Taylor, Astor, Varela, & Scranton, ; Taylor et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Osborne et al () showed that where temperature and [CO 3 2− ] trends diverge on longer time scales in Santa Barbara Basin, [CO 3 2− ] is the more important driver of area density. Similarly, over the course of the CARIACO time series, [CO 3 2− ] and primary productivity have decreased, while temperature has increased (Muller‐Karger et al, ; Taylor et al, ); thus, these latter two variables cannot be the primary drivers of area density over this interval. These lines of evidence all support the use of area density as a proxy to reconstruct long‐term trends in [CO 3 2− ] in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…From 1995–2018, the Cariaco Basin was the site of the CARIACO oceanographic time series (Muller‐Karger et al, ). As part of the time series, hydrographic measurements as well as bottle samples were collected to constrain carbonate chemistry.…”
Section: Introductionmentioning
confidence: 99%